Psoriasis and metabolic dysfunction-associated steatotic liver disease: an underestimated connection: a case report - Rodriguez-Suarez, Maria D. L. C.; Santoyo-Reza, César A.; Márquez-Alvarado, Carlos; Sotuyo-González, Alejandra S.; Ortuz-Lessa, Camila (International Journal of Research in Medical Sciences, 2025)
Psoriasis is a chronic inflammatory skin disease influenced by immunological, genetic, and environmental factors, and is closely linked to metabolic comorbidities such as metabolic dysfunction-associated steatotic liver disease (MASLD). MASLD is defined by hepatic fat accumulation in the presence of cardiometabolic risk factors such as obesity, type 2 diabetes, dyslipidemia, or hypertension. Both psoriasis and MASLD share inflammatory mechanisms, particularly involving the TNF‑α/IL‑23/IL‑17 axis, which promotes systemic inflammation, insulin resistance, steatosic liver disease, and fibrosis. We present the case of a 44-year-old man with untreated type 2 diabetes, active tobacco use, and chronic alcohol consumption, who presented with progressive abdominal distension, shortness of breath, and worsening of preexisting psoriatic lesions. Laboratory findings showed altered liver function, ultrasound confirmed ascites and grade, hepatic steatosis with fibrosis. A skin biopsy confirmed the diagnosis of psoriasis vulgaris. Initial treatment included non-selective beta-blockers, emollients, and therapeutic paracentesis, followed by referral to a tertiary care center. The coexistence of psoriasis and MetALD (a mixed form of MASLD and alcohol-related liver disease) worsens liver prognosis and limits the use of hepatotoxic drugs such as methotrexate. Therefore, early liver ultrasound in psoriatic patients with metabolic risk factors is essential to support safe therapeutic decisions and prioritize biologic treatments when liver damage is present.